Essential Oils - Bioactive Compounds, New Perspectives and Applications 2020
DOI: 10.5772/intechopen.91672
|View full text |Cite
|
Sign up to set email alerts
|

Algae Essential Oils: Chemistry, Ecology, and Biological Activities

Abstract: This chapter focuses on the essential oils and volatile fractions of seaweed. It includes an introduction to the essentials and volatile fractions and the main chemical classes found. This part is completed by a presentation of the fundamental aspects of biodiversity and the chemodiversity of the marine environment followed by the taxonomy and systematics of marine macroalgae. The heart of this chapter concerns the chemistry of volatile products extracted from marine algae. It reports the specificities of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 149 publications
(182 reference statements)
0
13
0
Order By: Relevance
“…Compounds from the chemical class of hydrocarbons, alkanes, and alkenes are common compounds in the majority of marine macroalgae EOs [1]. Although unsaturated hydrocarbons from C8 to C19 with the presence of 1 to 4 degrees of unsaturation are common, our study mainly reported the presence of compounds with one double bond.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…Compounds from the chemical class of hydrocarbons, alkanes, and alkenes are common compounds in the majority of marine macroalgae EOs [1]. Although unsaturated hydrocarbons from C8 to C19 with the presence of 1 to 4 degrees of unsaturation are common, our study mainly reported the presence of compounds with one double bond.…”
Section: Resultsmentioning
confidence: 74%
“…One of the main limitations of the use of algal materials in the food industry is their flavor, which is the main parameter of quality directly related to consumers' acceptance of food [2]. In comparison to the terrestrial odoriferous plants, only some algae possess an attractive, pleasant odor and characteristic marine flavor, and, therefore, great potential to be used in various food and cosmetic preparations [1,13].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations